Linguistic and functional-style features of Ukrainian advertising publications in the social network of Facebook - Pyatetska, Olga (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article analyzes the linguistic and functional-style features of advertising posts in the social network of Facebook on the example of the Ukrainian advertising agency "Kiwi Agency", whose purpose is to increase the process of selling and providing various commercial services on the media market; the main extralinguistic factors that influence the linguistic organization of this genre of Internet communication are determined. It has been established that advertising agencies that carry out an advertising campaign through the social network Facebook, attract SMM managers, copywriter and graphic designer. The main requirements for the creation of advertising posts are the uniqueness of the text, creativity, adaptability to the target audience, expressiveness, easiness of perception of information, call - to - action, correspondence of the text and its visual part. The conducted analysis of advertising publications made it possible to distinguish their main functions, which their structural and content features are related to: contact, call, information-entertaining, social, cognitive; find out the most important extralinguistic factors of the writing of posts, which include: purpose and communication tasks, adaptation to the target audience, information media, the influence of other languages ​​and cultures, etc., which led to the use englishisms, neologisms, created from the name of the brand of toys or abbreviation of the store "House of Toys", which is played by various variants: repetitions, alliteration, graphic means, rhyming, lexemes with affixes of an enlarged sign, exclamations, isotopes, imperative-vocative and nominative syntactic constructions; the use of speech techniques and allusions - the recognition of users of social media Facebook texts created by analogy with cartoons and famous songs. The article concludes that today in the language of Internet advertising as an effective marketing tool there are active processes of word formation, the tendency to simplify syntactic constructions, the growth of the role of visual means, mixing of styles.